1991
DOI: 10.1128/mcb.11.11.5693
|View full text |Cite
|
Sign up to set email alerts
|

AAR2, a gene for splicing pre-mRNA of the MATa1 cistron in cell type control of Saccharomyces cerevisiae.

Abstract: We have isolated a class of mutants, aar2, showing the a mating type due to a defect in al-a2 repression but with a2 repression activity from a nonmater strain of Saccharomyces cerevisiae expressing both a and a mating-type information in duplicate. Cells of the aar2 mutant

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Expression was assayed by primer extension, using 20 g RNA for GAL1 and 40 g RNA for GAL10 and ACT1. The primers used were GAL1-1 (CCTTGACGTTAAAGTATAGAGG), GAL10-1 (CAATGTATCCAGCACCACCTGT) (21), and ACT1-1 (AACCGT TATCAATAACCAAAGC) (33). GAL1 and GAL10 expression was quantitated and normalized to ACT1 expression.…”
Section: Methodsmentioning
confidence: 99%
“…Expression was assayed by primer extension, using 20 g RNA for GAL1 and 40 g RNA for GAL10 and ACT1. The primers used were GAL1-1 (CCTTGACGTTAAAGTATAGAGG), GAL10-1 (CAATGTATCCAGCACCACCTGT) (21), and ACT1-1 (AACCGT TATCAATAACCAAAGC) (33). GAL1 and GAL10 expression was quantitated and normalized to ACT1 expression.…”
Section: Methodsmentioning
confidence: 99%
“…Pre-U5 snRNP lacks the Brr2 helicase and instead includes the Aar2 protein (Gottschalk et al 2001;Boon et al 2007), which has been originally characterized as a factor involved in pre-mRNA splicing of the MATa1 transcript in Saccharomyces cerevisiae (Nakazawa et al 1991). We recently found that Aar2p and Brr2p bind, respectively, to an RNase H-like (RH) domain and a Jab1/MPN-like (Jab1) domain that lie next to each other in the C-terminal region of the Prp8 protein (Weber et al 2011).…”
mentioning
confidence: 99%
“…Aar2p was discovered as a factor involved in the splicing of some pre-mRNAs in yeast (Nakazawa et al 1991). While Aar2p is not required for splicing per se, removal of the protein blocked repeated rounds of splicing in vitro (Gottschalk et al 2001), suggesting that it could be involved in U5 snRNP or U4/U6-U5 tri-snRNP (re)assembly.…”
mentioning
confidence: 99%